2013
DOI: 10.1001/jama.2013.278932
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Surgery After Neoadjuvant Chemotherapy in Patients With Node-Positive Breast Cancer

Abstract: The use of sentinel lymph node surgery after neoadjuvant chemotherapy for patients who present with cN1 breast cancer provides an opportunity to avoid axillary lymph node dissection for those patients who have eradication of their nodal disease with chemotherapy. Since the initial publication of prospective trials demonstrating the false-negative rate of sentinel lymph node (SLN) surgery in this setting, this practice has been increasing. [1][2][3][4] A recent survey of the American Society of Breast Surgeons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
907
4
23

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,320 publications
(962 citation statements)
references
References 19 publications
28
907
4
23
Order By: Relevance
“…This will be particularly the case in patients who are receiving primary systemic therapy and who will be assessed for their response before undergoing definitive surgery. It has been shown that when this cohort of patients undergoes SNB, they have an elevated false negative rate (12%), which is potentially lowered on removal of three or more nodes (9%) [18]. If the suspicious nodes are clipped at ultrasound and removed at SNB, then the false negative rate may fall further to less than 2% [19].…”
Section: Future Perspectivementioning
confidence: 94%
“…This will be particularly the case in patients who are receiving primary systemic therapy and who will be assessed for their response before undergoing definitive surgery. It has been shown that when this cohort of patients undergoes SNB, they have an elevated false negative rate (12%), which is potentially lowered on removal of three or more nodes (9%) [18]. If the suspicious nodes are clipped at ultrasound and removed at SNB, then the false negative rate may fall further to less than 2% [19].…”
Section: Future Perspectivementioning
confidence: 94%
“…Although the standard of care was to perform an AD, the growing incidence of pCR in the axillary nodes led to the hypothesis that an SLNB could be justified in those patients. The ACOSOG-Z1071 study investigated the validity of SLNB after NAC for patients who were clinically positive before treatment but became clinically negative [32]. In this study, a pCR of 41% was found in the axilla after NAC.…”
Section: Reviewmentioning
confidence: 97%
“…The American College of Surgeons Oncology Group (ACOSOG)'s Z1071 trial and the Sentinel Neoadjuvant (SENTINA) study both reported errors in identifying the sentinel lymph node that exceeded the limit considered acceptable following chemotherapy. 32,33 It is not yet known whether slightly more false-negative findings could translate into unfavorable oncological results such as a greater incidence of recurrence of the disease and higher mortality. In those studies, the best and most acceptable results were obtained when two types of markers were used, a dye in association with radioactive technetium, and when more than two lymph nodes were removed.…”
Section: Figurementioning
confidence: 99%